Relationship between metabolic syndrome components in patients with resistant arterial hypertension - Shmakova, I. P.; Panina, S. A.; Shishova, P. A. (Journal of Education, Health and Sport, 2021)
Metabolic syndrome (MS) is a complex of interrelated pathological conditions based on insulin resistance, obesity, dyslipoproteinemia, arterial hypertension (AH). MS is a predictor of the cardiovascular disease, type 2 diabetes mellitus (DM), cancer and premature death. The incidence of type 2 diabetes increases with age and is 25.2% among the elderly. The prevalence of prediabetes or metabolic syndrome was approximately three times higher. Heart failure is another important cause of morbidity and mortality from the cardiovascular disease. Recent studies have shown that the incidence of hospitalizations for heart failure (adjusted for age and gender) was twice as high in patients with diabetes compared with patients without diabetes. Patients with hypertension and abdominal obesity (AO) have an increased risk of various complications: type 2 diabetes -5-9 times, stroke - 7 times, coronary heart disease - 4 times and mortality - 2 times. Objective: To analyze the relationship between the components of the metabolic syndrome in patients with resistant arterial hypertension (RAH). Materials and methods. A retrospective analysis of case histories of 120 patients, including 52 men (43.33%) and 68 women (56.67%) with a diagnosis of RAH and signs of MS. The presence of concomitant pathology, the level of office arterial pressure, pulse pressure (PP) were calculated; body weight, height with calculation of body mass index (BMI); waist circumference (WC), the levels of low-density lipoprotein (LDL) and high-density lipoprotein (HDL), triglycerides (TG), and plasma glucose were studied. Student's criterion was used to assess the degree of significance of the differences, p≤0.05 was taken as the critical level of significance. Pearson's correlation coefficient was used. Disorders of carbohydrate metabolism among patients with MS and RAH is 67.50%, of which type 2 diabetes makes 50.83%, impaired glucose tolerance - 16.67%. Patients with impaired carbohydrate metabolism are 2 times more likely to have complications of hypertension and lower HDL. Women with MS and RAH were significantly older than men and more often had concomitant pathology: morbid obesity (p <0.05), type 2 diabetes mellitus (p <0.05), chronic cerebral ischemia (p <0.05), higher body mass index (p <0.01). Strong correlation between WC and BMI (r = 0.707; p˂0.001), weak direct correlations between WC and PP (r = 0.231; p˂0.05) and WC and TG (r = 0.221; p˂0.05), weak feedback between WC and age (r = -0.188; p˂0.05), and for men direct correlations between WC and TG were confirmed (r = 0.454; p˂0.001), BMI and TG (r = 0.454, p˂0.002).